Annual-scale assessment of mid-20th century anthropogenic impacts on the algal ecology of Crawford Lake, Ontario, Canada - Matthew G. Marshall; Paul B. Hamilton; Krysten M. Lafond; Nawaf A. Nasser; Francine M.G. McCarthy; R. Timothy Patterson (PeerJ, 2023)
Meromictic Crawford Lake, located in SW Ontario, Canada is characterized by varved sediments, making it suitable for high-resolution paleoecological studies. Freeze cores, the only coring method available that reliably preserves the fragile laminations representative of seasonal deposition in the lake, were used to document siliceous diatom and chrysophyte community structure at an annual resolution from 1930–1990CE. Stratigraphically constrained cluster analysis identified major assemblage changes that are believed to have been caused by local, regional and possibly global anthropogenic impacts. The assemblage changes within the siliceous algae are attributed to regional weather and increased industrial emissions and related effects of acid deposition on the lake’s catchment associated with the Great Acceleration –the massive economic, industrial, and demographic expansion beginning in the mid-20th century. Observed increases in spheroidal carbonaceous particles (SCPs) in varved lake sediment dating to the early 1950s record rapidly expanding steel production without emission controls around 30 km upwind of the lake. The findings reported here reflect major changes in earth systems that the Anthropocene Working Group recommends for a proposed epoch to be termed the Anthropocene, providing support for the laminated sediments from Crawford Lake as a potential Global boundary Stratotype Section and Point (GSSP).